(untitled) (Heritage, 2021)
The subject of research in this paper is the analysis of the communication process which is by all means specific and different in the times of coronavirus. The pandemic caused by Covid-19 virus has appeared suddenly, spread astronomically fast, left enormous consequences and does not abate, affecting all the spheres of human life. The imposed changes of the life style have led to huge changes in human communication practice, the consequence of which is the social alienation which is omnipresent. The author researches to which extent the social isolation affects the human communication practice and whether people turn to virtual communication in the absence of direct human contact. The goal of this research is to determine in which way the use of modern technology and new media, primarily the internet and social networks, affects the sense of loneliness which inevitably appears during the pandemic and whether the use of modern technology helps to mitigate this sense of loneliness, if not eliminate it.